The Distribution of Isolects in Payung Sub-District, South Bangka Regency: A Dialectometric Study - Donal Fernado Lubis; Tri Arie Bowo; Resti Amalia (Master Program in Linguistics, Diponegoro University, 2026)
The present research aims to analyze the distribution of isolects in Payung Sub-district, South Bangka Regency, and determine their linguistic status within the southern Bangka dialect. Using a synchronic mixed-method approach, data were collected through interview and recording from 27 informants in eight observation points (OPs) using a 200-word Swadesh list. Dialectometric analysis was then applied to quantify the lexical and phonological distances between OPs. The results indicate that the variations in Payung Sub-district consist of sub-dialect and speech differences, with phonological differences ranging from 3% to 11%, marked by sound correspondence including diphthongization, vowel lowering, centralization, denasalization and lenition, while lexical difference ranges from 3% to 12,5%, implying the notion of retention, which native speakers refer to “bahasa kampong”. Geographically, while enclave regions maintain sub-dialectal features, variations are more frequently pronounced along the sub-district borderlines. This provides empirical evidence of a dialect continuum where the level of mutual intelligibility among sub-district is still high.